Analisis Cluster dalam Pengelompokan Kabupaten/Kota di Provinsi Jawa Timur berdasarkan Indikator Pendidikan - Diana Nafkiyah; Laely Rifatin; Muhammad Ricky Rozikin; Wara Pramesti (Universitas PGRI Adi Buana Surabaya, 2022)
Education can determine the quality of human resources. The better the quality of education, the more it will determine the direction of improving the quality of its human resources. The high and low level of education of the population can affect the dynamics of change or the quality of socio-economic life of the population of an area so that it is expected to be able to change the mindset of the community towards a more advanced direction. The importance of measuring and calculating the Education indicators in 2019 to see how far the distribution of education is in the Regency/City of East Java Province. The grouping of Education indicators in East Java in the form of APK, APS, APM, highest education completed, average length of schooling and AMH using the Cluster Hierarchy analysis method. By performing descriptive statistical analysis on the data, it can be seen that the population of districts/cities in East Java has various characteristics and quality of education. The growth of formal education at the level of high school education and equivalent has not been evenly distributed in every Regency/City of East Java Province. In the 2019 East Java Province Education indicator data, 2 groups of Regencies/Cities have the same tendency in the indicators. Based on the education indicator group formed, it can be concluded that the Regency/City in group 1 has a high average score on the SD certificate variable, which is 30.5719 compared to group 2, which means that the population aged over 10 years in the Regency/City in group 1 is more who have the last education up to elementary school equivalent. So it is hoped that the East Java Provincial Government will focus more on developing and equalizing the quality of education in the districts/cities included in cluster/group 1 so that the progress and welfare of the people of East Java Province can be achieved.